2009
DOI: 10.1159/000231527
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cutaneous Resonance Running Time in Cured Leprosy Subjects

Abstract: Background/Objectives: Leprosy prominently involves both the skin and peripheral neural tissues and some symptoms persist after microbial cure. Because alterations in the dermis also occur in leprosy, we assessed here whether there were changes in cutaneous resonance running time (CRRT), a parameter that is influenced by collagen properties, in cured leprosy subjects. Methods: A reviscometer was used to measure the CRRT at various directions on the dorsal hand and the flexural forearms of 76 cured leprosy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Previous studies have shown that changes of CRRTs occur in various cutaneous and systemic disorders (14,22,25). Besides decreased SC hydration, reduced CRRTs in psoriatic lesions are also demonstrated in present study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies have shown that changes of CRRTs occur in various cutaneous and systemic disorders (14,22,25). Besides decreased SC hydration, reduced CRRTs in psoriatic lesions are also demonstrated in present study.…”
Section: Discussionsupporting
confidence: 84%
“…And the acoustical shockwave running distance is 2 mm with energy of 1.77 μJ. Measurements were begun in the 12 o'clock position, which was determined with the right forearms laid on the table as described previously . Measurements were then taken clockwise at every 1 h interval or at every 30°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Courage–Khazaka Reviscometer RVM600 (Courage‐Khazaka Electronic, Koln, Germany) was used to measure the CRRTs on the central dorsum of the left hand, the forehead and the canthus. Measurements were initiated at the 12 o'clock position, which was determined with the hands laid on the table as described previously (30). Measurements were then taken clockwise at every 1‐h interval or at every 30°.…”
Section: Methodsmentioning
confidence: 99%
“…Its causative agent is Mycobacterium Leprae which parasitizes macrophages and Schawann cells. [1,2] The disease presents itself in different clinico-pathological forms depending upon the cellular immune system of the host. [3] Leprosy continues to be an important public health problem in most parts of Asia including India [4].…”
Section: Introductionmentioning
confidence: 99%